2009
DOI: 10.1177/1077558709342882
|View full text |Cite
|
Sign up to set email alerts
|

Provider Attitudes Associated With Adherence to Evidence-Based Clinical Guidelines in a Managed Care Setting

Abstract: In a cross-sectional observational study of Rochester (New York) primary care physicians (PCPs) enrolled in a pay-for-performance (P4P) collaboration, the authors investigated attitudinal factors associated with provider adherence to evidence-based clinical guidelines targeted by explicit incentives. The multivariable adherence model linked guideline adherence rates to provider attitudes among 186 survey respondents, adjusting for individual, practice, and community characteristics. Adherence was defined as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…We identified one prospective cohort, 9 two retrospective cohort, 10,11 and one pre-post study, 12 six cross-sectional surveys, [13][14][15][16][17] one economic analysis, 18 and two simulation studies. 19,20 Related to measure development, studies found that an emphasis on clinical quality and patient experience criteria was related to increased coordination of care, improved office staff interaction, and provider confidence in providing highquality care.…”
Section: Program Design Features (13 Studies)mentioning
confidence: 99%
See 4 more Smart Citations
“…We identified one prospective cohort, 9 two retrospective cohort, 10,11 and one pre-post study, 12 six cross-sectional surveys, [13][14][15][16][17] one economic analysis, 18 and two simulation studies. 19,20 Related to measure development, studies found that an emphasis on clinical quality and patient experience criteria was related to increased coordination of care, improved office staff interaction, and provider confidence in providing highquality care.…”
Section: Program Design Features (13 Studies)mentioning
confidence: 99%
“…10 Similarly, another study found that after controlling for covariates, perceived financial salience was significantly related to a high degree of performance. 13 Another study found that the underlying payment structure influenced performance, and that higher incentives may be necessary when the degree of cost sharing is lower. 9 Finally, a study examining the relationship between P4P and patient experience in California over a 3-year period found that, compared with larger incentives (>10%), smaller incentives were associated with greater improvement in provider communication and office staff interaction measures.…”
Section: Program Design Features (13 Studies)mentioning
confidence: 99%
See 3 more Smart Citations